2021
DOI: 10.3390/cells10113231
|View full text |Cite
|
Sign up to set email alerts
|

From Bench to Bedside: How the Tumor Microenvironment Is Impacting the Future of Immunotherapy for Renal Cell Carcinoma

Abstract: Immunotherapy has revolutionized the treatment landscape for many cancer types. The treatment for renal cell carcinoma (RCC) has especially evolved in recent years, from cytokine-based immunotherapies to immune checkpoint inhibitors. Although clinical benefit from immunotherapy is limited to a subset of patients, many combination-based approaches have led to improved outcomes. The success of such approaches is a direct result of the tumor immunology knowledge accrued regarding the RCC microenvironment, which, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 215 publications
(307 reference statements)
0
12
0
Order By: Relevance
“…Studies have shown that 25–30% of ccRCC patients already had distant metastases at the time of initial diagnosis [ 51 ]. So far, angiogenesis inhibition with tyrosine kinase inhibitors (TKIs) combined with the inhibition of immune checkpoint proteins such as PD-1/PDL-1 and CTLA-4 have revolutionized the treatment landscape of ccRCC patients with metastases [ 52 , 53 ]. However, the responses are limited to a subgroup of patients and only approximately 5 to 30% of patients will primarily progress [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 25–30% of ccRCC patients already had distant metastases at the time of initial diagnosis [ 51 ]. So far, angiogenesis inhibition with tyrosine kinase inhibitors (TKIs) combined with the inhibition of immune checkpoint proteins such as PD-1/PDL-1 and CTLA-4 have revolutionized the treatment landscape of ccRCC patients with metastases [ 52 , 53 ]. However, the responses are limited to a subgroup of patients and only approximately 5 to 30% of patients will primarily progress [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, RCC has been recognized as an immune-responsive tumor with a well-documented sensitivity to T cell attack [ 97 , 98 , 99 ]. Yet, RCC patients do not benefit substantially more from the T cell activating immune checkpoint blockade therapy compared to patients with tumors previously considered to be non-immunogenic [ 23 , 25 , 26 , 100 , 101 ]. This suggests the existence of additional layers of tumor-mediated immunosuppression beyond targeted T cell checkpoints that hamper antitumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Invigorating the T cell response through a blockade of the immune checkpoint molecules PD-1 or PD-L1, in combination with a blockade of the checkpoint CTLA-4 or with tyrosine kinase inhibition (TKI) has been approved as a first line treatment for advanced and metastatic RCC [ 23 , 24 ]. Despite some improvements in management of the disease through these T cell targeting therapies, only a fraction of patients has been shown to respond [ 23 , 24 , 25 , 26 ], suggesting that mechanisms beyond those directly targeting the T cells control the antitumor response. This underscores the critical need to better understand the tumor environment and to identify additional therapeutic targets beyond CTLA-4, PD-1 and PD-L1 to expand the range of patients that can be effectively treated.…”
Section: Introductionmentioning
confidence: 99%
“…These targets are involved in other neoplasia, and more importantly, the age of diagnosis of several cancers is a key factor that can influence the outcome of the applied therapy. In particular, immunotherapy is influenced by the age of the tumor host [ 9 ] and it is evident that most cancers are diagnosed in patients over 60. In this context, Damien Maggiorani and Christian Beauséjour focus on immune response and immune checkpoint inhibitor (ICI) therapy in older patients [ 10 ].…”
Section: Autoimmunity and Antitumor Responsementioning
confidence: 99%